Understanding the ambition in the EU's Strategic Compass: a case for optimism at last?. Issue 2 (3rd April 2022) - Sweeney, Simon; Winn, Neil
ABSTRACT: The quest for substance, capability, and strategic autonomy goes on – or does it? Is the objective of CSDP territorial defence and strategic autonomy, or crisis management and softer security concerns like peacekeeping, border management, protection of shipping lanes, and/or cyber security? The Union needs to move beyond familiar complaints about the lack of common strategic culture and EU intrusion into NATO responsibilities. Geostrategic and economic imperatives dictate that the EU should progress CSDP beyond civilian crisis management in the EU Neighbourhood, and military training and security sector reform (SSR). The Strategic Compass must signal CSDP clarity of objectives, coherence, enhanced capability, and appropriate burden sharing with NATO. The response to the Strategic Compass must build European strategic autonomy in ways that strengthen NATO. For military strategic and economic reasons, both the EU and the post-Brexit UK need intensive cooperation to maintain their geostrategic relevance and strengthen the NATO alliance. This paper reflects on prospects for the EU Strategic Compass and offers timely analysis of recent trends in EU foreign and security policy and expresses cautious optimism regarding the enhanced European strategic autonomy/actorness.